Impact of Conflicts in the DRC on Regional Trade: The Case of the EAC" - (:unkn) unknown (My University, 2022)
While it's true that regional processes on every continent are justified by economic or political objectives, historically, financial crises have led to a strengthening of Regional Economic Integration. By 2023, Africa will have nearly 14 different Regional Economic Communities (RECs). The aim of these RECs is to eventually facilitate Regional Economic Integration (REI) between the members of each region, and to pave the way for the larger African Economic Community (AEC) instituted by the Abuja Treaty. This treaty, signed in 1991 and in force since 1994, provides for the eventual creation of an African common market, of which the RECs form the basis. However, despite this multitude of RECs and the objective of creating a large African market, several countries, such as the Democratic Republic of Congo (DRC), are facing strong vulnerabilities due to the various shocks to which they are subjected, such as natural disasters, armed conflicts, etc. This research aims to analyze the various interactions between vulnerabilities caused by armed conflict and regional economic integration, focusing mainly on the Democratic Republic of the Congo, which, like other regional groupings, joined the Eastern African Community (EAC) in 2022.
Keywords: African Research